COMPARISON OF EPHEDRINE WITH PHENYLEPHRINE IN PREVENTION OF SPINAL ANAESTHESIA-INDUCED HYPOTENSION DURING CESAREAN-SECTION: A RANDOMIZED CONTROLLED TRIAL - ABDI , SSF; FAYYAZ , MA; SATTAR, MK; MOHSIN, MU; ISHAQUE , M (Biological and Clinical Sciences Research Journal, 2024)
Hypotension is a common complication of spinal anaesthesia during cesarean sections, with significant implications for maternal and neonatal outcomes. Effective management of spinal anaesthesia-induced hypotension is critical, and vasopressors such as ephedrine and phenylephrine are commonly used to maintain hemodynamic stability. However, their comparative efficacy and safety in the Pakistani population remain underexplored. Objective: To compare the efficacy and safety of ephedrine and phenylephrine in preventing spinal anaesthesia-induced hypotension during cesarean sections in a tertiary care hospital in Pakistan. Methods: This randomized controlled trial included 166 women undergoing elective cesarean sections at Ibne Siena Hospital and Research Institute, Multan, from May 2024 to November 2024. Patients were randomly assigned to receive either ephedrine (Group E, n=83) or phenylephrine (Group P, n=83) for the prevention of hypotension following spinal anaesthesia. Hemodynamic parameters, incidence of hypotension, and adverse effects were recorded. Data were analysed using SPSS version 26, with a p-value ≤0.05 considered statistically significant. Results: The incidence of hypotension was significantly lower in the phenylephrine group (30.1%) compared to the ephedrine group (50.6%) (p<0.01). Phenylephrine maintained better systolic blood pressure and mean arterial pressure throughout the procedure. Adverse effects differed between groups, with tachycardia more common in the ephedrine group (24.1% vs. 6.0%, p<0.01) and nausea slightly higher in the phenylephrine group (21.7% vs. 12.0%, p=0.08). No significant differences in neonatal Apgar scores were observed between groups. Conclusion: Phenylephrine is more effective than ephedrine in preventing spinal anaesthesia-induced hypotension during cesarean sections, with superior hemodynamic stability and fewer adverse effects. These findings support using phenylephrine as the preferred vasopressor in obstetric anaesthesia in resource-limited settings like Pakistan.